Perancangan Sistem Manajemen Keselamatan dan Kesehatan Kerja di PT. Cahaya Citrasurya Indoprima - Vincentius Ronaldo; Kriswanto Widiawan (Jurnal Titra, 2020)
Health and Safety Management System (SMK3) is a system management thoroughly covering the organizational structure, planning, responsibility, procedures, and resources it takes to execute health and safety management system (K3). The purpose of this thesis is to design SMK3 in accordance with Government Regulations number 50 of 2012 and still within the company’s ability to implement it.. The SMK3 design method consists of several sequential stages, initial audits, interviews about company capability, initial gap analysis, policy setting, the design of the implementation of K3, K3 monitoring design, the introduction of new K3 and the new audit. After designing the new audit, an initial gap comparison analysis phase is carried out. The new gap must be smaller than the old gap. If the old gap is smaller than the new gap, then the SMK3 design must be redone. The results of the preliminary audit showed that the company only meet 5 (4.09%) point assessment. The ideal percentage level is to meet as much as 60% of the assessment points. The final results of the design carried out resulted in appropriateness of evaluations totaling 118 (96.72%) points of assessment, so it can be said that the company has fulfilled the implementation of SMK3.